2011
DOI: 10.15835/nbha3926045
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Some Physico-Mechanical Nut and Kernel Properties of Two Walnut (Juglans regia L.) Cultivars

Abstract: Some physical such as length, width, thickness, mass, geometric mean diameter, sphericity and surface area and mechanical properties such as deformation at cracking, cracking force, energy absorbed and hardness of nuts and kernels were determined at three orientations first time for two walnut cultivars, namely 'Maraş-18' and 'Yalova-1' widely grown in Turkey. For nuts, the average length (45.48 mm), mass (12.70 g), geometric mean diameter (36.83 mm) and surface area (42.66 cm 2 ) were the highest in cv. 'Yalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…The mean value of length, width, and thickness of the ginkgo kernels were 20.58 (±1.46), 12.84 (± 1.17), and 12.24 (±0.98) mm, respectively. These values were higher than those reported for coriander seeds (Balasubramanian et al, 2012) and hemp seeds (Taheri-Garavand et al, 2012), but lower than for Parkia speciosa seeds (Abdullah et al, 2011) and for kernels of both varieties of walnuts (Maraj-18 and Yalova-1) (Ercisli et al, 2011). In comparison, it was found that the length of the ginkgo nut and its kernel was larger than that of the hazel nuts (Aydin, 2002), but for the width and the thickness, it was found that the hazel nuts and kernels were bigger than the ginkgo nuts and kernels, respectively.…”
Section: Resultscontrasting
confidence: 59%
See 3 more Smart Citations
“…The mean value of length, width, and thickness of the ginkgo kernels were 20.58 (±1.46), 12.84 (± 1.17), and 12.24 (±0.98) mm, respectively. These values were higher than those reported for coriander seeds (Balasubramanian et al, 2012) and hemp seeds (Taheri-Garavand et al, 2012), but lower than for Parkia speciosa seeds (Abdullah et al, 2011) and for kernels of both varieties of walnuts (Maraj-18 and Yalova-1) (Ercisli et al, 2011). In comparison, it was found that the length of the ginkgo nut and its kernel was larger than that of the hazel nuts (Aydin, 2002), but for the width and the thickness, it was found that the hazel nuts and kernels were bigger than the ginkgo nuts and kernels, respectively.…”
Section: Resultscontrasting
confidence: 59%
“…When compared to other seeds, it was found that the sphericity of the ginkgo nut was similar to that of an almond nut (Aydin, 2003), but lower than that of the pistachio (Pistacia vera L.) nut (Kashaninejad et al, 2006), filbert nut (Pliestic et al, 2006), and hazel nut (Aydin, 2002). The sphericity of the ginkgo kernel was found to be higher than that of Parkia speciosa seeds (Abdullah et al, 2011), almond kernels (Aydin, 2003), and pistachio kernels (Pistacia vera L.) (Kashaninejad et al, 2006), but lower than that of hazel kernels (Aydin, 2002) and the kernels of both varieties of walnuts (Maraj-18 and Yalova-1) (Ercisli et al, 2011). The mean mass of the nuts was 2.583 g (±0.298), while the kernels were found to be 2.083 g (±0.242).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This plant is native to central Asia and grows as a wild or semi-cultivated tree in a wide area from southeastern Europe and the Caucasus to Turkey and Iran, through southern portions of the former Soviet Union into China and the eastern Himalayas (Ercisli et al, 2011).…”
Section: Introductionmentioning
confidence: 99%